Efficiency of «Ectosan powder» in the fight against parasitic insects in pastures and animal halls for sheep - Prus, P.; Dovhii, Yu.; Zghozinska, O. (Scientific Progress & Innovations, 2022)
May - the end of October is the most optimal period of activity of zoophilous flies in the Polissia zone of Ukraine. In the case of a warm winter, insects remain viable throughout the year. In September-October 2020, among the zoophilic flies, the cow fly Leperosia ivitans L. (91%) was most often recorded on the pastures of private farms in the Novohrad-Volyn district of the Zhytomyr region. Autumn flies - Stomoxys calcitrans L. were less numerous. The cowbird Musca autumnalis and the viviparous field fly M. larvipara were also found. In the farms of the Radomyshl district, the autumn fireflies of the species St. calcitrans (85% among other flying insects). M. domestica houseflies were less numerous (15%). In addition to optimal seasonal weather conditions, favorable factors for the significant spread of insects in livestock premises and summer camps are also non-compliance with sanitary and hygienic requirements (untimely cleaning of manure, feed residues). Small cow stingers are localized as much as possible on the abdominal part of the udder and the head area of the sheep. Viviparous field flies M. larvipara and cow flies M. autumnalis are found on the head. Autumn fly-lighters St. calcitrans is registered on the thoracic, less often – pelvic limbs of sheep. The number of zoophilous flies increased significantly in the evening under cover under the condition of using artificial lighting. The use of insecticides and repellents is an integral part of protecting animals from ectoparasites. To protect sheep from the attack of dipterous blood-sucking insects in the warm season, the insecticide "Ektosan - powderTM" is used. It is applied to the coat at the rate of 5–10 g per animal. The applied drug "Ektosan powderTM" shows high repellent properties and a protective effect after treatment of sheep, which persists for up to three days (KVD over 75.3%). The relative protective effect lasts until the 5th day (KVD at the level of 62.3 to 78.1%).